Hamster oocyte membrane potential and ion permeability vary with preantral cumulus cell attachment and developmental stage - Emery, Benjamin R (BioMed Central, 2001)
BACKGROUND: In vitro maturation of mammalian oocytes is an area of great interest due to its potential application in the treatment of infertility. The morphological and physiological changes that occur during oocyte development are poorly understood, and further studies are needed investigating the physiological changes associated with oocyte maturation. In this study we evaluated the membrane potential and the sodium/potassium permeability ratio of oocytes acutely isolated, and cumulus-oocyte complexes in metaphase II and preantral follicle stages. RESULTS: Intracellular electrical recordings revealed that cumulus-enclosed oocytes have a membrane potential significantly more negative at the preantral follicle stage than at metaphase II stage (-38.4 versus -19.7 mV, p < 0.0005). The membrane potential of the cumulus-free oocytes was not different between the preantral and metaphase II stages. The membrane potential of the cumulus cells forming preantral stage follicles was shown to be significantly different from that of the oocyte within the follicle (-28.6 versus -38.4 mV, p < 0.05). The sodium/potassium permeability measured in cumulus-enclosed oocytes at the preantral stage equaled a mean value of 0.33. The ratio was significantly lower when measured in oocytes denuded of cumulus cells or cumulus-enclosed metaphase II oocytes, 0.76, 0.79, 0.77 respectively (p < 0.001). CONCLUSIONS: These data show a change in the membrane potential and Na(+)/K(+) permeability ratio during ooycte development from the preantral stage oocyte to the metaphase II stage. We have also demonstrated a change in the preantral oocyte membrane potential when surrounding cumulus cells are removed; either due to membrane changes or loss of cumulus cells.